An Analysis of Syntax and Academic Word Choice in Political News - Theangpitak, Wannarak (IJRDO- Journal of Educational Research, 2017)
English newspapers contain discourses with a variety of language usage fromthe real world. Therefore, English newspapers could be utilized as authentic materialsin an English study program or course to support English learning and teaching. Thisstudy aimed to explore a deeper insight how English grammatical structures andacademic word choices used in an English newspaper, based on Systemic FunctionalGrammar (SFG) by Michael Halliday and Academic Word List (AWL) by AverilCoxhead.The research results showed that the newspaper presented a variety of Englishsentences used in spoken and written discourses in the context of articles. Complexsentences were mostly utilized as a versatile writing technique. The academic wordswere accounted for 7.69% of the total words in the 250 news articles, and the mostfrequently presented words were “constitute” and “draft”. Some word families werenot found from the news articles; this might be due to some reasons that those wordswere likely irrelevant to political affairs or situations in the period of study such as“nuclear,” “medium,” or “series.”